Nonsyndromic Craniosynostosis and Associated Abnormal Speech and Language Development. Issue 1 (July 2017) - Naran, Sanjay; Miller, Matthew; Shakir, Sameer; Ware, Benjamin; Camison, Liliana; Ford, Matthew; Goldstein, Jesse; Losee, Joseph E.
Abstract : Background: Although many metrics for neurodevelopment in children with nonsyndromic craniosynostosis have been analyzed, few have directly examined early language acquisition and speech development. The authors characterized language acquisition and speech development in children with nonsyndromic craniosynostosis. Methods: The authors' institutional database was queried for nonsyndromic craniosynostosis from 2000 to 2014. Patients with an identified syndrome were excluded. Specific data elements included age, gender, velopharyngeal adequacy by means of the Pittsburgh Weighted Speech Scale, evaluation for anatomical motor delay, language acquisition delay/disorder, articulation or speech sound production delays/disorders, and whether speech therapy was recommended. Diagnosis of a submucous cleft palate was noted. Results: One hundred one patients met inclusion criteria, of which 57.4 percent were male. Average age at the time of the most recent speech evaluation was 6.1 years (range, 2.31 to 17.95 years); 43.6 percent had normal speech/language metrics and 56.4 percent had one or more abnormalities, including anatomical motor delay/disorder (29.7 percent), language acquisition delay/disorder (21.8 percent), articulation or speech production delay/disorder (4.0 percent), hypernasality (15.8 percent), and velopharyngeal insufficiency or borderline competency (23.8 percent). Average Pittsburgh Weighted Speech Scale score was 1.3 (range, 0 to 5), and 29.7 percent ( n = 30) of patients were recommended to have speech therapy. In addition, 25.8 percent of patients were diagnosed with a submucous cleft palate. Conclusions: One in four patients with nonsyndromic craniosynostosis carried a diagnosis of submucous cleft palate. The authors found that abnormal speech and language development occurs in one in 1.7 patients with nonsyndromic craniosynostosis, and that speech therapy for such abnormal development is warranted in one in 3.4 of them—a prevalence two to five times higher compared with the general pediatric population. Abstract : Psychosocial Insights for this Article is on Page 68e.